Application of Blog-Based E-Learning to Improve Cognitive Learning Outcomes and Independent Characters - Khotimah, Amalia Khusnul; Sutarto, Joko; Eko Nugroho, Sunyoto (Journal of Primary Education, 2021)
The roles of technology have influence on the progress of education, one of them is developed in education based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 65 of 2013 namely the use of information technology that is used to improve the efficiency and effectiveness of learning. The purpose of this study was to determine the effect of implementing blog-based e-learning in improving cognitive learning outcomes and independent characters in the thematic learning of fifth grade elementary school. This study used a quasy experimental design with two classes of research objects consisting of a control and an experimental class. The sample was 63 students. The result of this research shows that was that there was a significant increase in student learning outcomes and independent characters. The average increase in learning outcomes of 84% was in the very good category. In addition, the application of learning using blog-based e-learning in thematic learning makes the desire to compete enhance learning and be able to work independently is in the very high category. The average N-Gain test was of 0.49 which was in the medium category. It showed that the increase in cognitive learning outcomes in the experimental class using blog-based e-learning was more effective than the control class using google classroom.